Severe Complication of Uterine Perforation and Ileum Prolapse after Having Unsafe Abortion - Pradana, Aryando (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: Discuss complication after unsafe abortion and management of uterine perforation after curettage. Methods: Case report. Conclusion: Uterine perforation and ileum prolapse in this patient was a complication from unsafe abortion from unregistered health practicioner, fortunately the outcome is good, although actually it could be prevent. [Indones J Obstet Gynecol 2012; 36-3:150-3] Keywords: hysteroraphy, ileum anastomose, ileum laceration, ileum prolapse, ileum resection, incomplete abortion, uterine perforation